Characterization of Secondary Metabolites Profile of Flavonoid from Salam Leaves (Eugenia polyantha) Using TLC and UVSpectrophotometry - Syarifah, Anisa Lailatusy; Retnowati, Rurini; Soebiantoro, (Pharmaceutical Sciences and Research, 2019)
The flavonoids derived from Eugenia polyantha leaves were characterized by rapid and low cost approach. The aim of this research is to characterize secondary metabolite profile of flavonoids in the n-butanol fraction of E. polyantha using thin layer chromatography and ultraviolet-visible spectrophotometry. The n-butanol fraction was separated by using silica gel 60 GF254 as the stationary phase; chloroform: ethanol: glacial acetic acid (9.4: 0.5: 0.1) as the mobile phase; and visualized by using UV light 366 nm. Five isolates were obtained from the separation, but there were only three isolates (Rf 0.26; 0.44; 0.77) respectively identified as flavonoid compounds. The characterization of the isolates by UV-Vis spectrophotometry showing that the ranges of λmax were 250-280 nm (band II) and 310-360 nm (band I), which indicate the existence of flavone compounds. Further characterization of the three isolate using the AlCl3 5%/HCl 6 M solution showed that the λmax shifted from band I to the higher wavelength (bathochromic). The λmax shift indicated the existences of ketone at C-4, hydroxyl group at C-5, and orthodihydroxyl at ring B. According to the maximum wavelength, the result of the characterization showed that the flavonoid compounds of the n-butanol were 5,3’,4’-trihydroxyflavone3-C-glycoside or 5,4’,5’-trihydroxyflavone-3-C-glycoside; 5,6,3’,4’-tetrahydroxyflavone or 5,6,4’,5’-tetrahydroxyflavone; and 5,3’,4’-trihydroxyflavone or 5,4’,5’-trihydroxyflavone.